Insights to sulfur-resistant mechanisms of reduced graphene oxide supported MnOx-CeOy catalysts for low-temperature NH3-SCR. (August 2022) - Han, Qi; Jin, Shuangling; Wang, Jitong; Wang, Jiangcan; Sun, Pengfei; Zhou, Yang; Wang, Xiaorui; Zhang, Rui; Qiao, Wenming; Ling, Licheng; Jin, Minglin
Abstract: The MnOx -CeOy /rGO catalysts were prepared by a facile hydrothermal method for selective catalytic reduction (SCR) of NO with NH3 . Compared with MnOx -CeOy catalyst, the optimal MnOx -CeOy /rGO(0.1) catalyst not only shows an excellent low-temperature catalytic activity (60–180 °C), but also exhibits a better sulfur-resistant performance in the presence of 100 ppm SO2 +5 vol% H2 O at 160 °C. The in-situ DRIFTS results show that more NH4 + on Brønsted acid sites and NH3 on Lewis acid sites, as well as NH4 HSO4 are detected on MnOx -CeOy catalyst during SCR reaction with SO2, while the adsorbed NHx species over MnOx -CeOy /rGO(0.1) catalyst can be quickly activated and consumed via Eley-Rideal (E-R) reaction pathway. The highly dispersed Ce sites can effectively protect more Mn active sites from sulfation, and the Mn sites with stronger acidity and abundant oxygen vacancy defects promote the oxidative dehydrogenation of NH3 to form NH2, thus enhancing the sulfur resistance of MnOx -CeOy /rGO(0.1) catalyst. Graphical abstract: Image 1 Highlights: The MnOx -CeOx /rGO(0.1) catalyst shows good activity and excellent SO2 tolerance. The introduction of GO facilitates the dispersity of MnOx and CeOx nanoparticles. The generation of more Mn 3+ and Ce 3+ creates more surface oxygen vacancies. The acidic strengths of Brønsted and Lewis acid sites are enhanced. The adsorbed NHx species can be quickly activated and consumed via E-R pathway.